Bioeffects of Prunus spinosa L. fruit ethanol extract on reproduction and phenotypic plasticity of Trichoplax adhaerens Schulze, 1883 (Placozoa) - Maria Cristina Albertini; Daniele Fraternale; Federica Semprucci; Silvio Cecchini; Mariastella Colomba; Marco B.L. Rocchi; Davide Sisti; Barbara Di Giacomo; Michele Mari; Luigia Sabatini; Lucia Cesaroni; Maria Balsamo; et al. (PeerJ, 2019)
The aim of this work was to test and analyse the bioeffects of Prunus spinosa L. (Rosacaee) fruit ethanol extract on Trichoplax adhaerens Schulze, 1883 (Placozoa) laboratory cultures which—for the first time—were employed as in vivo biological model to assess the bioactivity of a natural extract. The ethanol extract of P. spinosa was administrated during a 46 day experimental period; ultrastructural (by optical, confocal, TEM and SEM microscopy) and morphometric analyses indicated that treated Trichoplax adhaerens showed significant differences in viability, reproductive modalities, body shape and colour with respect to the control group. Finally, P. spinosa bioactive compounds seem to exert profound protective effects on T. adhaerens reproduction and phenotype. Our results may support additional investigations related to other bioactive compounds properties useful for nutraceutical preparations to be used as food supplements.